(untitled) (Medical Forum Monthly, 2024)
Objective: Malignant ovarian tumors are one of the most lethal malignancies. The incidence of ovarian cancer is highest in Pakistan among all South Asian countries. It is 90% curable disease when diagnosed with stage I. Unfortunately, this disease is usually diagnosed in advanced stages, when it becomes symptomatic due to the abdominal dissemination of tumor. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Department of Pathology, BMSI, JPMC, Karachi from January 2011 to December 2015. Materials and Methods: The study material included 18 borderline and 84 consecutive samples of malignant epithelial ovarian tumors. The morphology was correlated with the age of the patients. The inclusion criteria were Properly fixed, paraffin embedded surgical pathological specimen with adequate tumor material. Results: Nearly 267 histopathologicaly proven cases of epithelial ovarian tumors were received in above mentioned five years. Out of these tumors 18 (6.7%) cases were borderline and 84 (31.2%) were malignant. Mucinous borderline tumor was commonest borderline tumor (72.2%). Serous cystadenocarinoma was the commonest malignant epithelial ovarian tumor (51%). Borderline ovarian tumors were seen between 21-40 years, whereas most malignant tumors were seen above 40 years. The observations and results of the study were elaborated with the assistance of tables, figures and photomicrographs. Conclusion: Malignant tumors out numbered the borderline ovarian tumors. The commonest borderline tumor was Mucinous borderline tumor. Among the malignant ovarian tumors, serous cystadenocarcinoma dominated the other types. Malignant ovarian tumors are more common above 40 years. Borderline tumors are commonly seen up to 30 years.